Lademanagement für Elektrofahrzeuge - Detzler, Sarah Katharina (KIT Scientific Publishing, 2017)
The present work describes a charging management with integrated charging optimization for electric vehicles that can be provided to a fleet by a fleet operator or to a group of private customers by a loading infrastructure operator. Aim of this charging optimization is the calculation of an optimized charging plan by considering the electricity price as well as hard capacity boundaries and user requirements. This charging optimization is designed and implemented within the scope of this work.